Жаһандану кезеңінде əлеуметтік мəселелер саласындағы мемлекеттің қызметі (Journal of actual problems of jurisprudence, 2019)
In this article is devoted to problem of social characters, analysis function of state in the sphere of socials problem in the period ofglobalization